The Use of Electronegativity and Hardness Towards Understanding Pearson’s Hard-Soft Acid-Base Principle - Dutta, Mala (Asian Journal of Chemistry, 2012)
The advent of Density Functional Theory [DFT] realizes the two new concepts namely electronegativity χ and hardness η. These two parameters have been very useful in understanding the insight of atoms, molecules, ions in isolated system, which are further extended to study the chemical reactions, namely double displacement reactions. These reactions were categorized on the basis of Pearson’s HSAB principle which indicates that hard-hard and soft-soft interactions are preferable to hard-soft interaction. The present work is devoted to some reactions and their feasibility on the basis of change in hardness (Δ η) and change in electronegativity (Δ χ).